Studies on Novel N4-[4,6-Diaryl-2-pyrimidinyl]-7-chloro-4-quinolinamine and their Microbicidal Efficacy - Arvind G. Mehta; Avnish A. Patel (E-Journal of Chemistry)
The required chalcones 1a-h were prepared by reaction of substituted acetophenone with different aryl aldehyde, which in turn treated with guanidine nitrate, yielded 4-(substituted phenyl)-6-(substituted phenyl)-2-pyrimidinamine 2a-h. Novel pyrimidine quinoline clubbed molecules 3a-h have been prepared by reaction of 2a-h with 4,7-dichloroquinoline. All the compounds were characterized by elemental analysis and spectral studies. The newly synthesized compounds were evaluated for their antibacterial and antifungal activity.